Sensory Perceptive and Discriminative Abilities of Patients with Occlusal Dysesthesia - Aridome, Kumiko; Ohyama, Takashi; Kino, Koji; Haketa, Tadasu; Baba, Kazuyoshi (Nihon Hotetsu Shika Gakkai Zasshi, 2005)
Purpose: It is not rare for dentists to come across patients who complain of several uncomfortable feelings of occlusion despite the absence of any observable occlusal anomaly or discrepancy. These kinds of symptoms are well defined by the term “occlusal dysesthesia”(OD). This study evaluated the cclusal perceptive and discriminative abilities in OD patients. Methods: The sensory perceptive and discriminative abilities were tested in 8 OD patients and 31 healthy subjects as controls. All of these subjects went through three types of tests: 1) thickness discrimination test by using occlusal registration foils, 2) thickness discrimination test by using bite block, and 3) mouth opening reproducibility test. Results: The median of the foil thickness discrimination ability of the control group was 14μm and that of the patient group was 8μm. In the bite block thickness discrimination test, both groups showed less than ±1mm thickness discrimination ability on average and were able to reproduce pre-indicated mouth opening with less than 10% error. There was no significant difference in these study results between the two groups. Conclusions: Sensory perceptive and discriminative abilities of OD patients were not significantly different from those of the healthy subjects in this study sample.